Use of Concept Mapping and Visual Learning Software in Education at Kuwait University - Safar, Ammar H; Alqudsi-Ghabra, Taghreed M; Qabazard, Nedaa M (Education (Chula Vista), 2012)
Information and communication technology (ICT) has been integrated as an educational tool in the late 1950's and the beginnings of 1960's. Many research and conceptual papers over the past decades have documented its importance on enhancing students' education and learning across all subject areas and grade levels. Our twenty-first century modern life is dominated by ICT, yet education has not been able to use ICT as an enabler and tool to foster effective learning fully. Concept mapping and visual learning software is a graphical application used to show and represent the relationship and connections among concepts. This study reviews the literature on the application of Inspiration software, a concept mapping tool that has been used with more than 25 million users worldwide. The study investigates the opinions of undergraduate students at Kuwait University (KU), their perceptions and willingness, for using concept mapping software to aid in learning. The study examines and identifies the usefulness of the application on students' learning and thinking. It also provides valuable contribution regarding the level of awareness, utilization, satisfaction, and difficulties faced by the uses of concept mapping software at KU. Furthermore, it explores beliefs of undergraduate students concerning the usefulness of this type of software on students' learning and thinking process. Findings of this research provide a profile and reference for policy and decision makers as well as professionals, working in the field of education and at the Ministry of Education and Higher Learning, regarding the integration of concept mapping and visual learning application software into education. (Contains 21 tables.)